Evaluation of the catalytic performance of different activated biochar catalysts for removal of tar from biomass pyrolysis. (15th December 2019) - Guo, Feiqiang; Peng, Kuangye; Liang, Shuang; Jia, Xiaopeng; Jiang, Xiaochen; Qian, Lin
Graphical abstract: Highlights: Biochar catalysts for tar removal were developed employing KOH, H3 PO4 and ZnCl2 . High surface area was achieved and new elements were introduced by activators. Excellent catalytic performance and high stability were achieved for tar cracking. The yields of H2, CH4 and CO increased significantly after tar catalytic cracking. Abstract: Biomass derived chars via simple synthesis methods play an important role in different applications due to their porous structure, low cost and potential for the catalysis research field. This work prepared three typical activated char catalysts using KOH, H3 PO4 and ZnCl2 as activators and rice husk as precursor for the catalytic decomposition of tar from biomass pyrolysis. Results showed that high surface areas were achieved and inorganic elements were introduced by applying the activators. The char obtained by KOH activation exhibited excellent catalytic performance on tar decomposition due to the high surface area and the presence of potassium compounds. Activation using H3 PO4 led to a more heterogeneous pore size distribution of biochar, also exhibiting high catalytic performance, while the activation of ZnCl2 might promote the agglomeration of zinc and rice husk containing inorganic matters, resulting in relatively lower tar conversion efficiency. The tar catalytic decomposition led to the significant increase in the yield of product gas, particularly the combustible gas components such as H2, CO and CH4 . GC-MS test results showed that macromolecular tar components were generally cracked and phenol was the main components of the residue tar, representing the good selectivity of the catalysts. The catalysts also showed excellent stability for tar cracking process and high catalytic performance was still achieved after five cycling tests. The biochar catalysts remained good porous structure with high surface area and the metals phases were well retained after five recycles, indicating that the biochar catalysts have the potential for long-term practical applications.